2011
DOI: 10.4028/www.scientific.net/kem.490.226
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Analysis of Stress and Strains in Flat Ends of High-Pressure Vessels

Abstract: Application of flat welded ends with stress relief grooves in high-pressure vessels is a common alternative to use of dished vessel ends. It is well established and follows calculation rules given in codes: EN-12952-3 [1], EN-13445-3 [2], or in ASME code [3]. However the calculation rules do not give any definite answer what should be the choice of parameters defining a circular stress relief groove, for example, position of the groove and its radius. Usually the choice of them relies on engineering practice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…For solving the IBVP an explicit 2nd-order time integration scheme was used. Szybiński et al [310] showed numerically the influence of parameters defining a circular stress relief groove, position of the groove and its radius on stresses and strains in flat ends of high-pressure vessels. The results were verified in experimental investigations.…”
Section: Junctions Of Shells Of Revolutionmentioning
confidence: 99%
“…For solving the IBVP an explicit 2nd-order time integration scheme was used. Szybiński et al [310] showed numerically the influence of parameters defining a circular stress relief groove, position of the groove and its radius on stresses and strains in flat ends of high-pressure vessels. The results were verified in experimental investigations.…”
Section: Junctions Of Shells Of Revolutionmentioning
confidence: 99%
“…Such geometries (optimal and nonoptimal with respect to the minimum value of the equivalent plastic strain) were selected after numerical optimization (finite element method). The obtained numerical and experimental results were compared and discussed in detail in the [12]. The performed numerical studies, verified by the experiments, revealed the presence of plastic zones which appeared in the cut-out regions.…”
Section: Introductionmentioning
confidence: 83%
“…The maximal value of the equivalent plastic strains for the nonoptimal configuration was several times higher than the respective one for the optimal groove configuration. Detailed results are given in [12]. The presence of such zones of plastic strains in the vicinities of the weld zones, in which material is also subjected to structural changes, may lead to a local increase in hardness and decrease in the fracture parameters in the weld and heat-affected zones [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FEM method is the one of the most common method in different kind of the engineering problems [54,62,66]. There are many publications devoted to FEM and its practical use, for example [79,42].…”
Section: Finite Element Methodsmentioning
confidence: 99%